Optimal Cross-Layer Scheduling for Multi-Access Cognitive Networks - Ghada Hatem Mohamed Saleh (2012)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2012 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Wireless Technologies; Dissertation, Academic